![image](https://tex.z-dn.net/?f=a%29+0%2C3-+x%5E%7B2%7D+%3D0+%5C%5C+-+x%5E%7B2%7D+%2B0%2C3x%3D0+%5C%5C+x%28-x%2B0%2C3%29%3D0+%5C%5C+x%3D0%2C-x%2B0%2C3%3D0+%3D%3Ex%3D0%2C3+%5C%5C+%0Ab%29+12-17x-5+x%5E%7B2%7D+%3D0+%5C%5C+-5+x%5E%7B2%7D+-17x%2B12%3D0+%5C%5C+5+x%5E%7B2%7D+%2B17x-12%3D0+%5C%5C+D%3D17%5E%7B2%7D%2B4%2A12%2A5%3D23%5E%7B2%7D+%5C%5C++x_%7B1%7D+%3D+%5Cfrac%7B-17%2B23%7D%7B2%2A5%7D%3D0%2C6%3B++x_%7B2%7D++%3D+%5Cfrac%7B-17-23%7D%7B2%2A5%7D%3D-4++%5C%5C+%0Ac%29+7x-4+x%5E%7B2%7D+%3D-15++%5C%5C+4+x%5E%7B2%7D+-7x-15%3D0+%5C%5C+D%3D7%5E%7B2%7D%2B4%2A15%2A4%3D17%5E%7B2%7D+%5C%5C++x_%7B1%7D+%3D+%5Cfrac%7B7-17%7D%7B2%2A4%7D%3D+-%5Cfrac%7B10%7D%7B8%7D%3D-1%2C25%3B++x_%7B2%7D+%3D+%5Cfrac%7B7%2B17%7D%7B2%2A4%7D++%3D3+)
x=0,3 \\
b) 12-17x-5 x^{2} =0 \\ -5 x^{2} -17x+12=0 \\ 5 x^{2} +17x-12=0 \\ D=17^{2}+4*12*5=23^{2} \\ x_{1} = \frac{-17+23}{2*5}=0,6; x_{2} = \frac{-17-23}{2*5}=-4 \\
c) 7x-4 x^{2} =-15 \\ 4 x^{2} -7x-15=0 \\ D=7^{2}+4*15*4=17^{2} \\ x_{1} = \frac{7-17}{2*4}= -\frac{10}{8}=-1,25; x_{2} = \frac{7+17}{2*4} =3 " alt="a) 0,3- x^{2} =0 \\ - x^{2} +0,3x=0 \\ x(-x+0,3)=0 \\ x=0,-x+0,3=0 =>x=0,3 \\
b) 12-17x-5 x^{2} =0 \\ -5 x^{2} -17x+12=0 \\ 5 x^{2} +17x-12=0 \\ D=17^{2}+4*12*5=23^{2} \\ x_{1} = \frac{-17+23}{2*5}=0,6; x_{2} = \frac{-17-23}{2*5}=-4 \\
c) 7x-4 x^{2} =-15 \\ 4 x^{2} -7x-15=0 \\ D=7^{2}+4*15*4=17^{2} \\ x_{1} = \frac{7-17}{2*4}= -\frac{10}{8}=-1,25; x_{2} = \frac{7+17}{2*4} =3 " align="absmiddle" class="latex-formula">